2022
DOI: 10.3390/antibiotics11020197
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Awareness among Undergraduate Students in Quito, Ecuador

Abstract: The inappropriate use of antibiotics leads to antibiotic resistance, which reduces their efficacy. The education of undergraduates is likely to influence their practices. Assessing awareness is critical in the general effort to confront the spread of antibiotic resistance. This cross-sectional investigation was carried out using the questionnaire “Antibiotic resistance: Multi-country public awareness” developed by the World Health Organization. Students from different backgrounds at the Central University part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…With respect to the familiarity with the four terms related to antibiotic resistance, the average level of knowledge was relatively low (2.52/4). This is consistent with previous research [ 21 , 39 ]. Students from developed countries, including Australia, France, Italy, and other European countries, have also acknowledged their need to learn more about antibiotic resistance [ 33 , 37 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…With respect to the familiarity with the four terms related to antibiotic resistance, the average level of knowledge was relatively low (2.52/4). This is consistent with previous research [ 21 , 39 ]. Students from developed countries, including Australia, France, Italy, and other European countries, have also acknowledged their need to learn more about antibiotic resistance [ 33 , 37 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…A professional translator translated the anonymous, closed, self-completed WHO questionnaire, “Antibiotic Resistance: Multi-country public awareness survey” [ 24 ] from English into Hebrew. This questionnaire is used among a variety of groups, including student populations, and it has been translated into different languages, e.g., [ 21 , 22 , 24 , 25 , 26 , 27 ]. After the questionnaire was translated into Hebrew, it was administered to five students who did not attend the college to ensure that the questions were comprehensible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This echoes the results of a previous study, which showed that 92.91% of students in the healthcare sector possess a good level of knowledge regarding AMR. 9 , 34 However, another study showed that medicine (66%) and pharmacy (95%) students had a better understanding of antibiotic resistance than nursing and other health science students. 35 A study of 425 medical students at the University of California showed that a programme focused on stewardship, which involved self-paced learning and a collaborative workshop, had an impact on the knowledge and attitudes of preclinical medical students, prompting them to work together for effective antimicrobial stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…These curricula should primarily focus on medicine, microbial virulence, mechanisms of resistance, and responsible antibiotic usage. 34 , 41 …”
Section: Discussionmentioning
confidence: 99%